To Study the Correlation of Serum Cholinesterase Level With Different Scoring Systems in Cirrhosis of the Liver - B S, Jagadeesh; K, Ravi; H R, Avinash; Gurav, Nitish Ashok (International Journal of Innovative Research in Medical Science, 2021)
Background: Chronic liver disease in the clinical context is a disease process of the liver that involves a process of progressive destruction and regeneration of the liver parenchyma leading to fibrosis and cirrhosis1. The serum cholinesterase is mainly synthesized in the liver and it is released into the blood, which is reduced in liver dysfunction due to reduced synthesis, marked reduction of cholinesterase in liver dysfunction and restoration of synthesis with hepatocyte recovery suggest serum cholinesterase activity might be a more specific marker of liver dysfunction than traditional liver function tests. Objectives: To estimate the level of serum cholinesterase in patients with cirrhosis of the liver. To correlate the level of serum cholinesterase with different scoring systems of cirrhosis of the liver and assess the utility of serum cholinesterase levels in prognostification. Materials and Methods: A cross-sectional, hospital-based, time-bound study conducted on 200 patients with cirrhosis of liver attending medicine OPD and getting admitted in hospitals attached to BMCRI from November 1st2016 to August 30th2018. All cirrhosis of liver patients were included and patients with Pregnancy, Acute infection, Chronic infection like tuberculosis and Oral contraceptive use were excluded. Serum cholinesterase, ultrasound abdomen, prothrombin Time, International Normalized Ratio, liver function test, Child-Pugh score, MELD score were measured. Results: In the study, the majority of the study subjects belonged to the age group 41 – 50 years (38.5%), followed by 31-40 years (21.5%), 51 – 60 years (18.5%). Sex distribution male 70% and female 30%. Serum Cholinesterase was positively correlated with Albumin and Prothrombin time and negatively correlated with MELD, Creatinine and Child-Pugh Score. The mean S. cholinesterase values found in study subjects belonged to Child-Pugh Score A, B and C were 4235.17 + 341.260, 3226.26 + 707.206 and 1764.09 + 808.797. The ANOVA results showed that there was a significant association found between child-pugh scores and S. cholinesterase (p – 0.001). Conclusion: The Study has demonstrated that the level of cholinesterase is correlated with the severity of the liver disease. Serum cholinesterase shows a good correlation with serum albumin, PT INR, Child-pugh score, MELD score. Compared to the above parameters serum cholinesterase is less complex and not easily affected by treatments for decompensated cirrhosis.